Safety assessment of intraportal liver cell application in New Zealand white rabbits under GLP conditions - Kafert-Kasting, Sabine; Meyburg, Jochen (Archives of toxicology, 2012)
Liver cell transplantation (LCT) is considered a new therapeutic strategy for the treatment of acute liver failure and inborn metabolic defects of the liver. Although minimally invasive, known safety risks of the method include portal vein thrombosis and pulmonary embolism. Since no systematic data on these potential side effects exist, we investigated the toxicological profile of repeated intraportal infusion of allogeneic liver cells in 30 rabbits under GLP conditions. Rabbit liver cells were administered once daily for 6 consecutive days at 3 different dose levels, followed by a 2-week recovery period. No test item-related mortality was observed. During cell infusion, clinical findings such as signs of apathy and hyperventilation, moderate elevations of liver enzymes ALT and AST and a slight decrease in AP were observed, all fully reversible. Cell therapy-related macroscopic and histological findings, especially in liver and lungs, were observed in animals of all dose groups. In conclusion, the liver and lungs were identified as potential toxicological target organs of intraportal allogeneic liver cell infusion. A NOAEL (no observed adverse effect level) was not defined because of findings observed also in the low-dose group. No unexpected reactions became apparent in this GLP study. Overall, LCT at total doses up to 12 % (2 % daily over 6 days) of the total liver cell count were tolerated in rabbits. Observed adverse effects are not considered critical for treatment in the intended patient populations provided that a thorough monitoring of safety relevant parameters is in place during the application procedure.